Entre figurantes e antagonistas: os kaingang no enredo da demarcação da terra indígena Iraí-RS - Araújo, Fábio (2018)
The present work discusses how the concepts of progress and modernity were used to try to prevent the demarcation of the Indigenous Land by Kaingang people from Iraí. The discourses invested against the Kaingang were based on the rhetoric that Indians weren’t in their traditional territory and promoted the deforestation and the pollution of the hot springs - an important natural resource commercially exploited by tourism. However, to understand historically the process in which these discourses arose, it’s necessary to analyze the airport construction in Iraí city – over traditional indigenous territory – and the historical and economic framework associated with it. Beside this, the emergence of the indigenous movement to demarcate its territory reflected in the proposition of a lawsuit by entities that called themselves environmentalists, to prevent the demarcation of indigenous land. This process, as well as some articles published in newspapers, especially the newspaper Zero Hora, were used as main sources of this research. As hypothesis, it’s accepted that the preservationist discourses were triggered from the Kaingang movement for demarcation, with the intention to hiding the real motive: to prevent the demarcation of the Kaingang de Iraí Indigenous Land, and to maintain commercial exploitation of the hot springs by political agents and private companies interested in the profits from this tourist activity.